Pengembangkan Perangkat Pembelajaran Menggunakan Software Cabri 3D Materi Bangun Ruang Sisi Datar Dengan Metode Problem Solving Yang Berorientasi Pada Kemampuan Berpikir Kritis Dan Prestasi Belajar Siswa SMP - Daud Daud; Rusgianto Heri Santoso (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2019)
The development of science and technology rapidly growth in use right now, learning device which used inadequate so that the knowledge of students about the technology lagged and limited learning devices used in school. Devices learning of mathematics are effective and in accordance with the subject matter has not developed as expected, and development in the field of education is very important to improve the quality and the quality of resources man. This suggests that education should be made a major priority by both Governments, the education community and Manager. Improve the quality of education endeavors to improve the quality of human resources. This gave the impetus for the Government to always trying to fix and improve the quality of education at every level of education. Technological developments in recent decades go very quickly in line with the development of technology, including computer networks. Various supporting technologies and applications have also been developed in an effort to support and facilitate the activities of human life and organization, including teaching and learning activities in the world of education. In General, the device is software to deliver information or messages from one place to another. The device used in the learning process, including teaching and learning activities.